Ketentuan Kodefikasi Pneumonia Kasus Rawat Inap pada Pasien Jaminan Kesehatan Nasional (JKN) berdasarkan ICD 10 - Iqbal, Muhammad Fuad (Jurnal Rekam Medis & Manajemen Infomasi Kesehatan, 2022)
Pneumonia is a disease that attacks the respiratory system due to infection from viral/bacterial aspiration and radiation and other causes, if not treated properly it can worsen the patient's condition, causing an increase in treatment costs. In the era of the National Health Insurance (JKN), the Indonesian Case Base Groups (INA CBG's) system was an important element in the submission and payment of claims for payment of health services that had been carried out by health care facilities, based on the ICD 10 code for diagnosis and ICD 9 CM for the procedure in processing claim. Coder staff must proficient in codification and clinical pathways for each disease because the Health Insurance Administration Agency (BPJS) has rules for every diagnosis. Based on the dispute claim, the INA CBG claim problems in 2018 are determined for the diagnosis of pneumonia as follows: (1) pneumonia whose cause is not specified can be coded J18.9, (2) pneumonia with pulmonary TB must use the join code to A16.2, (3) pneumonia with COPD using the merge code to J44.0, except for acute exacerbations of COPD, coded separately (4) pneumonia with septicemia is coded separately unless medical investigations reveal Streptococcus pneumonia using combined code A40.3, (5) pneumonia with typhoid fever using the combination code A01.0† J17.0* and (6) pneumonia with asthma were coded separately. These provisions must be understood by coders in coding cases of pneumonia to avoid suspension so that the claim process runs smoothly and works efficiently